Not so long ago, and not so far away: Where is there room for oppressed people in fandom?. (1st March 2019) - Goward, Shonda L.
The word fandom has come to mean a group of people who share the common interest in a thing, and is often associated with comic books, science fiction and fantasy art. For racially minoritized and/or working-class fans, fandom is complicated because their love of the art can only go so far because often they do not see themselves represented in the art itself. Thus, one cannot begin to discuss the nuances of how the lives of people of colour and/or working-class people are represented until they are in the work at all. This article discusses the author's inability to engage in a fan-based pedagogy in her work both as an educator in the classroom and as an administrator because it would mostly include students from the dominant ethnic and class groups and leave her own groups still 'othered' on campus.